1990
DOI: 10.1210/jcem-71-5-1322
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Mechanism by which Androgens Enhance Mitogenesis and Differentiation in Bone Cells*

Abstract: Recently, we reported a direct effect of androgens on murine and human bone cells to stimulate bone cell proliferation and differentiation. To test whether this effect of androgenic steroids might be mediated by growth factors, we measured relative concentrations of insulin-like growth factor-I and -II (IGF-I and IGF-II) and transforming growth factor-beta (TGF beta) in the conditioned medium from androgen-treated murine calvarial cell cultures. Only the concentration of TGF beta was increased. Consistent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
1
5

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(61 citation statements)
references
References 33 publications
2
53
1
5
Order By: Relevance
“…TIEG has been recognized as a transcription factor, that mediates some effects of TGF-b (129,130). Of interest, the decrease in TGF-b and TIEG mRNA levels paralleled growth inhibition of 5a-DHT in this cell line (44), indicating that TGF-b may indeed mediate the effects of androgens on osteoblast proliferation (44,126).…”
Section: Tgf-bmentioning
confidence: 85%
See 2 more Smart Citations
“…TIEG has been recognized as a transcription factor, that mediates some effects of TGF-b (129,130). Of interest, the decrease in TGF-b and TIEG mRNA levels paralleled growth inhibition of 5a-DHT in this cell line (44), indicating that TGF-b may indeed mediate the effects of androgens on osteoblast proliferation (44,126).…”
Section: Tgf-bmentioning
confidence: 85%
“…Estrogen is known to stimulate both de novo synthesis of TGF-b and activation of latent TGF-b (110,122,125). Several groups have demonstrated that androgens (5a-DHT, testosterone, and DHEA) increase TGF-b gene expression (31,126) and activity (127), suggesting that at least part of the positive effects of androgens may be mediated by an osteoblast-derived increase in TGF-b production and activity. In support of this hypothesis are the findings of an in vivo study conducted on male rats (128).…”
Section: Tgf-bmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, McCormick et al reported that early onset of puberty in females was related to differences in BMD values between the sexes during puberty [25]. It was recently shown that sex steroids have receptors and exert biologic effects on both epiphyseal cartilage cells [1,7] and bone cells [5,21]. In these studies, it was suggested that these hormones play an important role in skeletal growth and mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for such interaction exists in other androgensensitive systems with regard to receptors for epidermal growth factor (prostate; Mulder et al, 1989) and transforming growth factor (bone; Kasperk et al, 1990). More recently, the expression of hepatocyte growth factor/scatter factor (HGF/SF) has been demonstrated in osteoblasts (Blanquaert et al, 1999), stromal cells of mouse prostate (Sasaki and Enami, 1999) and myoid cells of rat testis (Catizoni et al, 1999).…”
Section: Discussionmentioning
confidence: 99%